Transmission of SARS‐CoV‐2 through breast milk and breastfeeding: a living systematic review. Issue 1 (28th August 2020) - Centeno‐Tablante, Elizabeth; Medina‐Rivera, Melisa; Finkelstein, Julia L.; Rayco‐Solon, Pura; Garcia‐Casal, Maria Nieves; Rogers, Lisa; Ghezzi‐Kopel, Kate; Ridwan, Pratiwi; Peña‐Rosas, Juan Pablo; Mehta, Saurabh
Abstract: The pandemic of coronavirus disease 2019 (COVID‐19) is caused by infection with a novel coronavirus strain, the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). At present, there is limited information on potential transmission of the infection from mother to child, particularly through breast milk and breastfeeding. Here, we provide a living systematic review to capture information that might necessitate changes in the guidance on breast milk and breastfeeding given the uncertainty in this area. Our search retrieved 19, 414 total records; 605 were considered for full‐text eligibility and no ongoing trials were identified. Our review includes 340 records, 37 with breast milk samples and 303 without. The 37 articles with analyzed breast milk samples reported on 77 mothers who were breastfeeding their children; among them, 19 of 77 children were confirmed COVID‐19 cases based on RT‐PCR assays, including 14 neonates and five older infants. Nine of the 68 analyzed breast milk samples from mothers with COVID‐19 were positive for SARS‐CoV‐2 RNA; of the exposed infants, four were positive and two were negative for COVID‐19. Currently, there is no evidence of SARS‐CoV‐2 transmission through breast milk. Studies are needed with longer follow‐up periods that collect data on infant feeding practices and on viral presence in breast milk. Abstract : The objective of this review is to assess available evidence related to the possible transmission of SARS‐ CoV‐2 through breast milk and through breastfeeding (i.e., related bodily fluids, such as blood, sweat, and respiratory droplets) or droplet transmission due to close contact with the infant or young child via skin‐to‐skin exposure or airborne transmission. The review aims to support policymakers in making evidence‐informed global, regional, and national guidelines on infant feeding in the context of the ongoing pandemic.